"Fallen Between the Cracks": Exploring Subsidized Housing From the Perspectives of Low-Income Preseniors. Issue 1 (2nd January 2020) - Walsh, Christine A.; Gulbrandsen, Cari; Hewson, Jennifer; Paul, Karen
Abstract: Older adults aged 55 to 64 are vulnerable to housing insecurity and homelessness due to complex, interacting factors including decreasing options for employment, poor health, changing life circumstances, and ineligibility for seniors' benefits or seniors' subsidized housing. Despite the vulnerability of low-income preseniors, few researchers have examined the housing experiences of this population. This participatory action research study was guided by an advisory committee ( n  = 11) comprised of individuals with lived experiences of homelessness and service providers. We conducted in-depth, qualitative individual interviews with low-income preseniors ( n  = 30), who experienced housing insecurity or homelessness, to better understand their unique challenges and barriers to obtaining affordable, safe and suitable housing. Low-income preseniors ( n  = 6), who had direct experience with housing insecurity or homelessness, collaborated with the data analysis process. The constant comparative method was used to identify themes related to: (1) risk factors for homelessness, (2) barriers in securing housing, (3) characteristics of desirable and undesirable housing, and (4) the importance of advocacy in addressing the complex challenges they encounter. Study findings also highlighted the influence of contextual and structural factors that contribute to the preseniors' quality of life, health, and well-being as they age. Recommendations are provided to inform subsidized housing practices, policies, and services targeted at meeting the unique needs of this population.